The Effectiveness of Training Mental States on the of Theory of Mind among Intellectual Disabled Children - mehdi abdolahzade; narges adib; mriam hasanzadeh; masomeh pourmohamad; abasali iazdani (Ravānshināsī-i Afrād-i Istis̠nāyī, 2014)
The theory of mind describes the ability of predicting and attributing mental states of self and others; and is essential for one’s social interaction. Previous studies show that intellectually disabled children have deficient and immature theory of mind. The present study wants to survey the effectiveness of training mental states on acquisition and promotion of theory of mind of students with intellectual disabilities. In this semi-experimental study, 60 intellectually disabled male and female students were selected by the multiple cluster sampling method in the city of Tehran. These students were randomly assigned into two groups: 30 students (15 boys and 15 girls) were placed in the experimental group and 30 others (15 boys and 15 girls) were placed in the control group. To assess the theory of mind the 38-Item Theory of Mind Test, and unexpected task, were used for both groups in pretest and posttest. The experimental group received nine sessions of training mental states, and the control group used normal school education. To analyze the data, covariance was used. The results revealed that the scores of theory of mind in experimental group was significantly higher than the control group (p<0.05). Training mental states is effective on acquiring and promoting the theory of mind in intellectually disabled students.